Peer pressure, time management and academic performance of female secondary school pupils in Ibadan metropolis, Oyo State, Nigeria (2021)
This study investigated peer pressure, rime management and academic performance of female secondary school students in Ibadan Metropolis, Oyo State, Nigeria The descriptive survey research design was adopted for this study. A sample of 310 respondents was selected through multi-stage sampling procedure. Two hypotheses were tested. A questionnaire tagged "Peer pressure, time management and academic performance " was used for data collection. Pearson Product Moment Correlation (PPMC) was the major statistical tool employed for data analysis. The findings revealed a significant relationship between peer pressure and academic performance of female secondary school students in Ibadan Metropolis, Oyo State. Nigeria (r=0.650. p<0.05). li was a/so shown that time management and academic performance of female secondary school students in Ibadan Metropolis. Oyo State. Nigeria were significantly related (r=0.715. p<0.05). Il was also revealed that the joint contribution of the two variables (peer group and time management) was significant in the prediction of academic performance of female students (F = 8.375. p<0.05). Based on the findings from the study, it was recommended that female secondary school students should be made to cultivate the act of wise utilisation of time. Among other things that there should be counselors in all secondary schools to help students guide against negative peer pressure; parents should provide proper monitoring of their children so as to prevent the influence of bad friends: teachers, lecturers, schools and institutions should enact rules and provide adequate supervision for students to guide against peer pressure influence